Environmental justice beyond race: Skin tone and exposure to air pollution - Sandra Aguilar-Gomez; Juan Camilo Cardenas; Ricardo Salas Diaz (Proceedings of the National Academy of Sciences, 2025)
Recent research, focused mostly on the United States and Western Europe, shows that marginalized communities often face greater environmental degradation. However, the ethnoracial categories used in these studies may not fully capture environmental inequality in the Global South. Moving beyond conventional ethnoracial variables, this study presents findings exploring the link between skin tone and fine particulate matter (PM 2.5 ) exposure in Colombia. By matching household geolocations from a large-scale longitudinal survey with satellite-based PM 2.5 estimates, we find that skin tone predicts both initial pollution exposure levels and their changes over time. Although average exposure levels remained stable during our study period, the environmental justice (EJ) landscape in Colombia contemporaneously underwent a complete transformation. In 2010, lighter-skinned individuals faced higher PM 2.5 exposure, but darker-skinned individuals experienced steeper increases in the following years. By 2016, the EJ gap had reversed, with people with the darkest skin tones exposed to PM 2.5 levels nearly one SD higher than those faced by people with the lightest skin tones. These patterns remain robust when controlling for a comprehensive set of theoretically relevant covariates, including ethnoracial self-identification and income. Disproportionate exposure to pollution from fires partially explains the observed disparities. Decomposition analysis shows that this variable, local collective action, and economic marginalization account for a sizeable share of the EJ gap. However, one-third of the gap remains unexplained by observable characteristics. With climate change intensifying fire incidence, the disproportionate disease burdens that vulnerable groups face might deepen unless policy measures are taken to reverse this trend.